Leibniz. From metaphysical dogmatism to idealism of the intellectuality of the universe - López, Diana María (ARFIL y UNL, 2020)
Hegel recognizes in the “ideality” of the monad a necessary antecedent for the logical-ontological understanding of “being for itself” (Fürsichsein) in the context of overcoming the opposition between finite and infinite of the logic of being, at the same time that the anticipation of the idealistic formulation of the principle “substantiality is subjectivity”. For the purposes of verifying this thesis, this article begins with the notions of “representation” and “idealism” from which Kant allows himself to associate Leibniz’s doctrine with a “metaphysical dogmatism”, since Hegel presupposes their knowledge. To pass in a second moment to Hegel's critical position regarding the “ideality” of the monad, in which it is measured with the contribution of interpretations that German idealism itself –transcendental, first, and subjective, later– was generating.